The Short- And Longer-Term Effects of a Child Labor Ban - Caio Piza; André Portela Souza; Patrick M. Emerson; Vivian Amorim (Institute of Labor Economics (IZA), 2022)
Are bans effective at lowering child labor and increasing school attendance and, if so, do these effects lead to positive outcomes later in life? This paper seeks to answer these questions by examining the effect of a 1998 Brazilian law that increased the minimum employment age from 14 to 16. To examine this question we use two different regression discontinuity designs to analyze Brazilian household data. We find that the ban had no overall impact across affected children in Brazil, but that it led to a significant decrease in the labor market participation of urban boys, whose paid labor dropped 35 percent, driven mainly by a decrease in informal work. We also find a concomitant 10 percent increase in the share of urban boys only attending school. Interestingly, we find that by age 18 this cohort was still almost 20 percent less likely to have a paid job and was less likely to be economically active even when they were legally allowed to work. However, we find no evidence that the impact of the ban lasted over time as reflected in measures of educational attainment, employment rates, and wages. Our results suggest that when enforced, bans on child labor can have significant immediate impacts amongst affected populations, leading to a decrease in work and an increase in school attendance. It remains unclear if these impacts translate to improved adult outcomes.
Keywords: C21; J08; J22; J24; K31; 330; child labor; education; labor laws